Hubungan pola konsumsi minuman beralkohol terhadap kejadian hipertensi pada tenaga kerja pariwisata di Kelurahan Legian - Jayanti, I Gusti Ayu Ninik; Wiradnyani, Ni Ketut; Ariyasa, I Gede (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: Â The shift in lifestyle in tourism environment in Legian Village triggers alcohol consumption. Excessive consumption of alcoholic beverages will have an impact on long-term health of one of them increased levels of cortisol in the blood so that the activity of rennin-angiotensin aldesterol system (RAAS) increases and causes blood pressure to rise.Objectives: To determine the correlation between consumption patterns of alcoholic beverage with incidence of tourism labor hypertension in Legian. Methods: Design of crossectional study with sample of 87 tourism worker. Blood pressure measurement using Sphygmomanometer and stethoscope. The consumption pattern of alcoholic beverages is obtained by using the form of SQ-FFQ (Semi Quantitative Food Frequency Qualitiative).Results: The most common type of alcoholic beverage is beer with a percentage of 40.2%. A total of 48.3% of respondents consumed alcoholic beverages with a mild amount and as much as 56.3% of respondents often consumed alcoholic beverages. There was a significant correlation between beverage type and hypertension (rs = 0.433), total consumption and hypertension (rs = 0.566).Conclusion: There was a significant correlation between consumption pattern of alcoholic beverages with incidence of hypertension in tourism labor in Legian Village